Dampak Etos Kerja Dan Lingungan Kerja Fisik Terhadap Kinerja Pedagang Kaki Lima Car Free Day Simpang Lima Gumul Kab.Kediri - Intan Rangga Amartiya (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2023)
The impact of the work ethic which consists of indicators of a person's interpersonal skills, an individual's initiative in carrying out work, and being reliable in doing his work. The physical work environment which consists of indicators of lighting, air temperature, cleanliness, security, working hours in carrying out work is very important to find out how big the impact is on the performance of street vendors Car Free Day Simpang Lima Gumul Kab. Kediri. By knowing this relationship, parties from the Bodronoyo community, including street vendors at the Simpang Lima Gumul car free day, Kab. Kediri can estimate how the consumer response and the impact of the work ethic and physical work environment that is generated / given so that it can provide even better performance and service by street vendors, especially in the Bodronoyo community in the future. This research is a research that is included in mixed research or a combination of quantitative methods and qualitative methods. The sampling technique in this study used a purposive sampling technique (where the samples used were based on certain criteria determined by the researcher). The samples used or taken in this study were street vendors at the Simpang Lima Gumul car free day, Kab. Kediri based on certain criteria determined by researchers and processed as respondents. Data obtained through observation, questionnaires or questionnaires, documentation, interviews and literature. From the results of the analysis carried out, the results of the study show that the work ethic and physical work environment have a significant impact simultaneously on performance. It is known that the results of the correlation analysis are as follows: The R Square value is 0.524 or 52.4% and the remaining 0.476 or 47.6% is influenced by other variables not examined in this study.